The leader's guide to resilience : how to use soft skills to get hard results - Tang, Audrey (Leader's guide (Pearson (Firm)), 2021)
"This book offers easy-to-action tips and strategies rooted in theory and effective in practice to help you, your teams and your organisations withstand the surrounding pressures, and continue to grow. This book offers accessible methods to survive the challenges you - and your teams - may be facing both professionally and personally, as well as means to recover, rebuild and strengthen your resources to not only withstand and rebound from adversity, but actually grow"--